The impact of the use of amalgam in dental treatment on the prevalence of restless legs syndrome in older people - Magdalena Szklarek; Tomasz Kostka (Nofer Institute of Occupational Medicine, 2019)
Background The link between restless legs syndrome (RLS) and the number of amalgam fillings in older people was investigated. Restless legs syndrome decreases the quality of life and impairs normal functioning. Mercury (in amalgam) may be toxic to nerve cells and may account for the incidence of RLS. Material and Methods The relationship between RLS and the presence of amalgam in the teeth of 104 people aged 60-97 years old was determined. By using 4 questions, together with the diagnostic criteria from the internationally used questionnaire produced by the International Restless Legs Syndrome Study Group (IRLSSG), authors assessed the extent of the symptoms and occurrence of RLS. Careful medical history and medical examination were used for ascertaining each subject's type of restorative materials (i.e., amalgam or other metal) and the number of such fillings. Results Subjects who answered "yes" (indicating presence of RLS) to the 4 subsequent questions had a significantly higher number of amalgam dental fillings as compared to the subjects without RLS symptoms. Presence of other metal dental restorative materials and the number of amalgam dental fillings reported in the past had no significant influence on RLS symptomatology. Conclusions Authors conclude that while examining the correlates of the appearance of restless legs syndrome the use of amalgam in the dentition should be taken into account. Med Pr. 2019;70(1):9-16